Gender-specific aspects and contemporary assessment of thromboembolic complications in atrial fibrillation (literature review) - D. V. Duplyakov; L. V. Shekhovtsova; D. A. Shebonkina (Рациональная фармакотерапия в кардиологии)
The article examines the evolution of risk assessment strategies for thromboembolic complications in patients with atrial fibrillation (AF), with a focus on the role of gender in the CHA2DS2-VASc score, which has long been the standard for stroke risk stratification. The analysis of historical approaches of various feasibility study risk assessment strategies, starting from the recommendations of 2001, when there was no single risk assessment, to the current international guidelines of 2024, led to the conclusion that special attention should be paid to the expediency of including female sex as an independent stroke risk. Current data indicate that gender identity has been leveling off over time in the incidence of strokes among patients with AF and suggest considering the female sex only as an age-dependent modifier of stroke risk. The results of studies from different countries (Finland, Denmark, Great Britain) confirm a decrease in the influence of the female sex as an independent stroke risk factor, discussing the expediency of switching to a simplified CHA2DS2-VA score (excluding gender). The authors emphasize the importance of individualized episodic re-evaluation of thromboembolic complications risk, particularly in patients with comorbidities, and also emphasize the need for caution when implementing changes in domestic practice, considering the unique characteristics of Russian healthcare and its disparities with systems in other countries.